2018
DOI: 10.1155/2018/2939307
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Xuefu Zhuyu Decoction Pretreatment on Myocardium in Sepsis Rats

Abstract: Xuefu Zhuyu Decoction (XFZYD), the classical recipe for promoting blood circulation by removing blood stasis, has been used in China for a long history clinically. XFZYD has been found to improve cardiac function through reducing inflammation. However, the effect of XFZYD on myocardial apoptosis remains unclear. Herein, we investigated the mechanism of XFZYD preconditioning on myocardial injury in sepsis rats. The rats were treated with XFZYD one week, followed with intraperitoneal injection of lipopolysacchar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 21 publications
0
21
0
1
Order By: Relevance
“…Interestingly, our in vivo data showed that XFZYD decreased cell migration and invasion at the low dose (the concentration of 0.0125 g/ml for cell migration and that of 0.05 g/ml for ocular tumor invasion) but increased cell migration and invasion at a high dose (the concentration of 0.1000 g/ml for both). Collectively, the effects of XFZYD on cell migration and tumor invasion in Drosophila displayed a dose-independent and biphasic manner, whereas, in a septic shock rat model, XFZYD may reduce myocardial damage and a protective role for the heart structure and function in a dose-dependent manner [41]. Besides, we have noticed that the doses of XFZYD that affect cell migration and tumor invasion are different, which may be due to distinct genetic backgrounds of two fly models.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Interestingly, our in vivo data showed that XFZYD decreased cell migration and invasion at the low dose (the concentration of 0.0125 g/ml for cell migration and that of 0.05 g/ml for ocular tumor invasion) but increased cell migration and invasion at a high dose (the concentration of 0.1000 g/ml for both). Collectively, the effects of XFZYD on cell migration and tumor invasion in Drosophila displayed a dose-independent and biphasic manner, whereas, in a septic shock rat model, XFZYD may reduce myocardial damage and a protective role for the heart structure and function in a dose-dependent manner [41]. Besides, we have noticed that the doses of XFZYD that affect cell migration and tumor invasion are different, which may be due to distinct genetic backgrounds of two fly models.…”
Section: Discussionmentioning
confidence: 86%
“…As a representative of blood-activating stasis-resolving recipe, XFZYD is mainly used to treat metabolic syndrome and cardiac-cerebral vascular diseases, including hyperlipidemia, hypertension, coronary heart disease, traumatic brain injury, and ischemic stroke [34][35][36][37][38][39][40]. It has been reported that XFZYD displays a significant effect on the pretreatment of the myocardium in sepsis rats by inhibiting myocardial cell apoptosis and antioxidation [41]. In addition, researchers found that XFZYD could protect against retinal ischemic by downregulating HIF-1α and VEGF via a synergistic inhibition of RBP2 and PKM2 [42].…”
Section: Introductionmentioning
confidence: 99%
“…The TCM herbal formulas are still keeping updated in the modern medical practice of CVD control. For example, the standardized Xuefu Zhuyu decoction (XFZY) has been a treatment of blood stasis (AS) since the 19th century in China (Yang et al, 2017;Lin et al, 2018;Meng et al, 2018). To reinforce the therapeutic effects of XFZY, we creatively added in new compounds into XFZY and further formed a new formula termed TongMai ZhuYu decoction (TMZY), which has been reported to exhibit significant clinical efficacy on AS (Ji et al, 2012;Ji et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Given the limitations of Western medicine in preventing and treating CIN, traditional Chinese medicine might provide a complementary therapy for it. According to the previous studies, Xuefu Zhuyu decoction suppressed the oxidative stress reaction [15][16][17] which played an important role in the development of CIN [18][19][20] although the precise mechanisms of CIN were not completely elucidated. erefore, we speculated that Xuefu Zhuyu decoction might contribute to reduce CIN after PCI probably through suppressing the oxidative stress reaction.…”
Section: Introductionmentioning
confidence: 99%